Fatigue amongst Icelandic police officers : prevalence and implications - Franz Jónas Arnar Arnarson 1993- (2021)
A sample of 151 active police officers in Iceland, which represented approximately 20% of the Icelandic police force, was analysed. A mixed method approach was used to assess the prevalence of insomnia symptoms along with the prevalence of depression, anxiety, and stress, as well as how they might experience fatigue. Icelandic translations of the BIS, PHQ-9, and the DASS-21 were used as well as questions that were related to their work experience and how they experienced fatigue. All of the scales used, proved to be valid and reliable. Scores on the BIS indicate that 70.1% of Icelandic police officers had the presence of insomnia. Police officers that had an indicator of the presence of insomnia scored significantly higher on the PHQ-9 and all of the subscales of DASS-21 indicating that police officers that sleep poorly are at greater risk of depression, anxiety, and stress compared to police officers that sleep well. Police officers that reported to mainly be working a daytime job, reported significantly fewer instances of feeling so sleepy/tired that it affected them at work or in their private life and also had a significantly lower mean score when compared to police officers that reported to work shifts. Compared to an older study amongst Icelandic police officers the ratio of depression symptoms was similar, the ratio of stress symptoms was lower, and the ratio of anxiety symptoms was higher. The prevalence rates of depressive and anxiety symptoms were similar to what has been found internationally amongst police officers. Most of the police officers reported feeling a difference in their well-being, mental state and physical condition due to their work arrangement noting that night shifts had the worst effect. Participants also noted to struggle with work/life balance due to shift work and fatigue. Implications and further research was discussed. Keywords: police, police officers, fatigue, sleep, insomnia, depression, anxiety. 151 íslenskir lögreglumenn, u.þ.b. 20% af heildarþýðinu tóku þátt í ...